Improved Scheduling Procedure for Intensify Resource Utilization in Heterogeneous Cloud Environment - Singh, Lovejoban Preet; Kumar, Anil (International Journal of Computer Sciences and Engineering, 2025)
Resource allocation is critical to investigate the need for resources in substantially enhancing every day. To tackle this issue our proposed policy presents a new hybrid strategy known as the fittest job firefly algorithm(FJFFA) which sorts the jobs in the queue according to least cost and maximum profit. This queue is presented to firefly algorithm. Jobs are again sorted randomly and presented to firefly algorithm. The solution thus obtained from the algorithm is superior. Makespan and Flowtime obtained as a result is improved by 6%.